Analysis of Communication Patterns of Gocar Drivers in Improving Services to Customers in Makassar City - Restu Satriana Montalili; Muh. Iqbal Sultan; Alem Febri Sonni (Program Studi Pendidikan IPS, 2025)
This study aims to explain the communication patterns carried out by Gocar drivers in improving and maintaining their services to customers in Makassar City. A driver is said to be able to fulfill the standard of service procedures if they carry out the rules that have been set, such as the minimum and maximum number of passengers in a day so that the partner's target is met to get a reward or bonus from the online application provider. Not only that, the assessment of the customer (user) to the online transportation provider application partner also greatly affects the driver's performance. The research method used is qualitative with a case study approach. Means of observation, in-depth interviews, and literature study carried out data collection techniques. The results showed that online transport impacts and influences people's transport needs. But behind that, partners as parties who cooperate with online transportation provider applications are also required to provide their best service performance to customers (users). Starting from driving skills, how to behave, driving equipment, and even how to communicate to maintain the driver's performance. As a sign or measure of an online transport driver's ability to carry out his duties well, this provider application provides an assessment space for customers. The assessment after booking on the application in question is the provision of star marks by the customer on the service felt during the trip.